Robotic intersphincteric resection of low rectal cancer versus laparoscopic intersphincteric resection of low rectal cancer - Alotaibi, Ahmed Z. (International Journal of Advances in Medicine, 2024)
This systematic review evaluated and compared the two currently available intersphincteric resection techniques (robotic and laparoscopic intersphincteric resection) for low rectal cancer, with the final aim of comparing associated factors between the two techniques. The assessed factors included surgical duration, hospital stay, complications, overall survival, local recurrence, and low anterior resection syndrome (LARS). A literature search of the search engines “PubMed”, “SCOPUS”, and “Web of Science” was conducted, with a time interval set between 2015 and 2023. The initial search yielded 57 studies, of which 10 met the inclusion and exclusion criteria. Hence, data was extracted from only these 10 studies. The average reported robotic surgery time varied between 197 and 472 mins, while the laparoscopic surgery time varied between 240 and 325 mins. Conversely, the overall survival and local recurrence rates were 89.7% and 6.7% for robotic and 87.9% and 6.2% for laparoscopic resection, respectively. In addition, complications were reported in 16.5% and 18.2% of robotic and laparoscopic resection cases, respectively. This systematic review showed that although the surgery duration is longer in robotic resection compared to laparoscopic resection, the former technique is associated with lower rates of complications and local recurrence, and improved overall survival. In addition, few studies have reported on the prevalence of LARS; therefore, we recommend that this field be studied and included in the reported data of the upcoming studies to allow more conclusive evidence regarding prevalence of LARS among the two groups of intersphincteric resections.